Detecting Linguistic Traces of Destructive Narcissism At-a-Distance in a CEO’s Letter to Shareholders - Craig, Russell (Journal of business ethics, 2011)
Destructive narcissism is recognized increasingly as a serious impairment to good corporate leadership and ethical conduct. The Chief Executive Officer’s letter to shareholders (an important formal corporate communications medium) has potential to provide linguistic traces of destructive narcissism and insight to aspects of corporate leadership and the ambient ethical culture of a company. We demonstrate this potential through selective analyses of the letters of the Chief Executive Officers of Enron, Starbucks, and General Motors.